Relationship between Parasagittal Perivenous Cysts and Leakage of Gadolinium-based Contrast Agents into the Subarachnoid Space around the Cortical Veins after Intravenous Administration - Naganawa, Shinji; Ito, Rintaro; Nakamichi, Rei; Kawamura, Mariko; Kawai, Hisashi; Taoka, Toshiaki; Yoshida, Tadao; Sone, Michihiko (Magnetic Resonance in Medical Sciences, 2021)
Purpose: The purpose of this retrospective study was to investigate the relationship between the number and size of cystic structures around the cortical veins near the superior sagittal sinus and the leakage of gadolinium-based contrast agent (GBCA) around the cortical veins.Methods: Of 190 patients (91 male and 99 female), that were scanned at 4 h after an intravenous injection of GBCA as a diagnostic examination for endolymphatic hydrops, 6 patients with GBCA leakage were younger than the previously proposed threshold age of 37.3 years for leakage. Six age-matched patients without leakage were also included for reference. In addition, we included 8 cases without leakage that were older than the hypothesized threshold of 37.3 years, as well as 8 age-matched patients with GBCA leakage into the cerebrospinal fluid space. The number of cysts was counted and the sizes were measured in these 28 patients (age: 32–60 years old, 13 men and 15 women).Results: The mean number of cysts surrounding the cortical veins in the parasagittal region was 4.29 ± 1.77 vs. 1.79 ± 1.05 (P = 0.0001) in the subjects with and without GBCA leakage, respectively. The mean size of the largest cysts was at 8.89 ± 3.49 mm vs. 5.69 ± 2.29 (P = 0.009) in the subjects with and without GBCA leakage, respectively.Conclusion: The number and size of the perivenous cystic structures near the superior sagittal sinus is greater in subjects with GBCA leakage into the subarachnoid space compared with those without leakage. Future research regarding the histological and functional details of these parasagittal cystic structures is needed.